Profil Kemampuan Perncanaan Karir Siswa di SMA Kabupaten Pemalang - Susanto, Aditiyo Susanto (MEDI KONS: Jurnal Prodi Bimbingan dan Konseling UNISRI Surakarta, 2022)
The background of this research is that the results of the questionnaire on the needs of students that I gave to class XI, especially in class XI IPS 1, there are 3.16% of students who are still unsure of their choice of ideals, 3.31% of students who still do not understand the study program in higher education, and there are 2.86% of students who do not understand the relationship between talents, interests, education, and work . In addition, a simple interview was also conducted with one student at a different school. The results of the interviews showed that these students were still low in planning their careers. This shows that students in their career planning are still low. The ability of students to plan a career will support the success of their career goals. Conversely, if the ability to plan his career is low, it will have a bad impact on his career goals. The main problem studied is the Profile of Students' Career Planning Ability in SMA Pemalang Regency.The research method used is a survey research method with a quantitative approach that aims to reveal something as it is. The population in this study were all students of class XI SMA in Pemalang Regency which consisted of 4 State Senior High Schools. The try out will be held at SMA Negeri 1 Pemalang in class XI IPA 1 with 36 students. The sampling technique in this research is using cluster random sampling technique. The analysis used to test the validity is product moment correlation and reliability using the alpha formula. The calculation results of the career planning ability questionnaire can be seen that the lowest score is 15 respondents in the very high category with a percentage of 19%, 22 respondents in the high category with a percentage of 28%, 43 respondents in the medium category with a percentage of 54%, 0 respondents in the low category with a percentage of 0%, and 0 respondents in the very low category with a percentage of 0%. Suggestions that researchers can convey should be guidance and counseling teachers have an active role but guidance and counseling teachers must develop or improve career guidance services in schools. Keywords: Career Planning.